Pancreatic cancer diagnosis by free and exosomal miRNA - Zöller, Margot (World journal of gastrointestinal pathophysiology, 2013)
Patients with pancreatic adenocarcinoma (PaCa) have a dismal prognosis. This is in part due to late diagnosis prohibiting surgical intervention, which provides the only curative option as PaCa are mostly chemo- and radiation resistance. Hope is raised on a reliable non-invasive/minimally invasive diagnosis that is still missing. Recently two diagnostic options are discussed, serum MicroRNA (miRNA) and serum exosomes. Serum miRNA can be free or vesicle-, particularly, exosomes-enclosed. This review will provide an overview on the current state of the diagnostic trials on free serum miRNA and proceed with an introduction of exosomes that use as a diagnostic tool in serum and other body fluids has not received sufficient attention, although serum exosome miRNA in combination with protein marker expression likely will increase the diagnostic and prognostic power. By their crosstalk with host cells, which includes binding-initiated signal transduction, as well as reprogramming target cells via the transfer of proteins, mRNA and miRNA exosomes are suggested to become a most powerful therapeutics. I will discuss which hurdles have still to be taken as well as the different modalities, which can be envisaged to make therapeutic use of exosomes. PaCa are known to most intensely crosstalk with the host as apparent by desmoplasia and frequent paraneoplastic syndromes. Thus, there is hope that the therapeutic application of exosomes brings about a major breakthrough.
Gesehen am 02.08.2021